1991
DOI: 10.1111/j.1600-051x.1991.tb01123.x
|View full text |Cite
|
Sign up to set email alerts
|

The finding of antiplaque features in Acacia Arabica type of chewing gum

Abstract: The gum of Acacia Arabica is described in the British pharmacopoeia as a source of useful medicaments. It is believed to be of value for treating gingivitis and for reducing plaque. 2 blind crossover trials were carried out to evaluate the antiplaque potential of Acacia gum compared with sugar free gum. In trial 1, the mean gingival and plaque scores were lower after 7 days of using Acacia compared with sugar-free gum but the differences were insignificant. In trial 2, daily photographic assessment of erythroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…The reduction in plaque and gingivitis scores in Group I (placebo) can be attributed to the Hawthorne effect (i.e., patients frequently appear to improve merely from the effects of being placed in a clinical trial). 17 Similar to studies by Lindhe et al 18 and Triratana et al, 19 prophylaxis and scaling were not carried out prior to the experimental phase of the present clinical study, unlike other studies by Gazi et al 20 and Brecx et al in which oral prophylaxis was carried out prior to the experimental phase. 4 Porphyromonas gingivalis and Prevotella intermedia are strongly implicated in the pathogenesis of chronic periodontitis 21 and the proteolytic activity of P. gingivalis is recognized as a potential virulence factor.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…The reduction in plaque and gingivitis scores in Group I (placebo) can be attributed to the Hawthorne effect (i.e., patients frequently appear to improve merely from the effects of being placed in a clinical trial). 17 Similar to studies by Lindhe et al 18 and Triratana et al, 19 prophylaxis and scaling were not carried out prior to the experimental phase of the present clinical study, unlike other studies by Gazi et al 20 and Brecx et al in which oral prophylaxis was carried out prior to the experimental phase. 4 Porphyromonas gingivalis and Prevotella intermedia are strongly implicated in the pathogenesis of chronic periodontitis 21 and the proteolytic activity of P. gingivalis is recognized as a potential virulence factor.…”
Section: Discussionmentioning
confidence: 40%
“…Gazi concluded that Acacia gum has the potential to inhibit early plaque formation although the long-term effect may not be there. 20 The anti-inflammatory activity of Barleria prionitis, another ingredient of gumtone gel, is proved by Singh et al 'TAF', an active fraction from the plant Barleria prionitis, exhibited significant anti-inflammatory activity against different inflammagens like carrageenan, histamine and dextran along with the inhibition of vascular permeability. 24 Another constituent of formulation is Terminalia chebula, the extract of which strongly inhibits growth, sucrose induced adherence and glucan induced aggregation of Streptococcus mutans.…”
Section: Discussionmentioning
confidence: 99%
“…It is an economically valued timber tree and is used for agricultural implements and fuel wood, while the leaves are used for infodder (Anonymous 1985). The gum of A. arabica is described as a source of useful medicaments, and it is believed to be of value for treating gingivitis and for reducing plaque (Gazi 1991); the flowers of Acacia raddiana was used to attract and catch Anopheles sergentii (Müller and Schlein 2006); A. arabica was reported as insecticidal plant which can be used in insecticide preparation (Singh and Saratchandra 2005); the bioefficacies were evaluated for their oviposition inhibition, residual toxicity, and direct toxicity effects on pulse beetle, Callosobruchus maculatus (Rahman and Talukder 2006); ash was used to control the grain weevil, Sitophilus granarious (Rahman et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Lupeol present in the bark has an anti-inflammatory activity and tannins have antibacterial and antioxidant properties. [2526]…”
Section: Discussionmentioning
confidence: 99%